TINJAUAN KEAMANAN PANGAN, HYGIENE SANITASI DAN KANDUNGAN GIZI MAKANAN TRADISIONAL DI KABUPATEN TABANAN - Ni Putu Widyartini; I Gst Putu Sudita Puryana; Anak Agung Nanak Antarini (Meditory : The Journal of Medical Laboratory, 2020)
Traditional food is food made in the traditional way using traditional materials and equipment. Traditional foods consist of complete meals, side dishes, vegetables and traditional snacks that are in high demand by local and national tourists so that their safety needs to be tested. The purpose of this study is to determine the Food Safety, Sanitation Hygiene and Nutrition Content of Traditional Traditional Foods Tabanan Regency. This type of research is observational with cross sectional study design. Traditional Foods of Tabanan Regency there are 103 food samples and the sample size used is 30 samples (19%) of the total sample. Food safety contained 15 (50%) exceeded the maximum limit for coliform contamination and 1 (3%) sample exceeded the limit of Escherichia Coli contamination. Hygiene Traditional food sanitation all food safety scores from traditional food processors are included in the category of vulnerable but safe for consumption. Nutritional content of traditional foods in complete foods contains high energy, namely 321,9g (14.3%) of adequacy, in side dishes containing high protein 11,6g (19.2%) of adequacy and fat that is 20,8g (32%) of adequacy, in vegetables containing high fat which is 8g (12,3%) of adequacy and in snacks contain high carbohydrate which is 67,2g (18.7%) of adequacy.Keywords: Traditional Food, Food Safety, Sanitation Hygiene, Nutrition